Cognitive Behavioral Therapy (CBT) Approach with Bibliotherapy Techniques to Improve Early Adult Students' Marriage Readiness - Harlina, Desi; Firman, Firman; Netrawati, Netrawati (Widyagogik, 2023)
Marriage readiness is needed by every individual who has entered early adulthood. Marriage readiness is basically important to study because marriage readiness is the basis for making decisions with whom to marry. This study aims to analyze the effectiveness of the cognitive behavior therapy approach with bibliotherapy techniques in increasing marriage readiness in early adult college students. This type of research is quantitative research using an experimental research design. The experimental design used in this study is the One Group Pre-test-Post-test. The sample in this study were 40 students. Data were analyzed using non-parametric statistical formulas with a Wilcoxon-signed level test.